Paediatric Medicines: Formulation Considerations - Roque, Fátima (Archives of Pharmacy and Pharmaceutical Sciences, 2017)
The use of unlicensed and off-label medicines in children is widespread and has raised an increasing concern over the last years. The majority of medicines taken by children are extemporaneously compounded by pharmacist, and there is a lack of information regarding bioavailability, suitability and stability. These formulations must be prepared from pure active substance and not from commercially available dosage forms. The development of paediatric formulations, particularly those suitable for very young children, can be a challenge to pharmacists. There is limited knowledge available about the acceptability of different dosage forms, administration volume, dosage form size, taste, safety of formulation excipients regarding to age and development status. The selection of formulation and route of administration depends on the disease being treated and the clinical condition. European Guidelines and reflection papers recommend that pharmaceutical development should consider some parameters like capability, acute or long-term illness, caregiver convenience, disability, culture differences and formulations more attractive to children must be explored.